Administration of thiamazole for Graves' disease might trigger the onset of type 1 diabetes. Issue 5 (14th June 2018) - Mizutani, Gen; Hikima, Yusuke; Satomura, Atsushi; Iuchi, Takujiro; Nakajima, Ritsuko; Miyashita, Yumi; Yasuda, Shigemitsu; Oikawa, Yoichi; Isshiki, Masashi; Inoue, Ikuo; Noda, Mitsuhiko; Shimada, Akira
Abstract : Thiamazole might trigger the onset of type 1 diabetes.